Twitter for professional use in electrophysiology: practical guide for #EPeeps. Issue 8 (8th April 2021) - Linz, Dominik; Garcia, Rodrigue; Guerra, Federico; Kommata, Varvara; Bollmann, Andreas; Duncker, David
Abstract: Social media (SoMe) becomes more and more popular in the cardiological community. Among them, Twitter is an emerging and dynamic medium to connect, communicate and educate academic and clinical cardiologists. However, in contrast to traditional scientific communications, the content provided through SoMe is not peer-reviewed and may not necessarily always represent scientific evidence or may even be used to unjustifiably promote therapies for commercial purposes. For the unintended, this means of communication might be appear difficult to handle. This article aims to provide a practical guide on how to use Twitter efficiently for professional use to keep yourself up-to-date about new techniques, the latest study results and news presented at national or international conferences. Additionally, important limitations will be discussed.